Tending the Soil: How to Grow a Successful Faculty Peer-Mentoring Group - Hudson, Jennifer (Academic Leader, 2026)
When a new faculty member is hired at a university, having trusted colleagues and faculty mentors who help navigate a path to growth, belonging, and success is essential.
Keywords: dept.aa

Early college program implementation and growth: a collaborative initiative by a state university - Yavuz, Olcay; Milburn, Trudy (Concurrent Enrollment Review, 2025)
This article explores a collaborative initiative undertaken by a state university aimed at implementing and expanding an Early College Program. The conceptual framework, practical strategies, collaborative efforts and background of this initiative are presented. With a focus on improving college access for all, the article introduces the university's efforts to promote an inclusive Early College Program accessible to high-need students in particular. This collaborative approach highlights the importance of fostering collaboration among both internal and external partners of Institutions of Higher Education (IHE). By sharing insights into the program design and implementation, the article aims to inspire similar initiatives and contribute to the ongoing dialogue promoting early college experiences for all.
Keywords: Conceptual framework; Focus (optics); Focus group; Higher education; Program evaluation; State (computer science); dept.aa; dept.edl

Not all fun and games: videogame labour, project-based workplaces, and the new citizenship at work - Milburn, Trudy (Journal of Broadcasting & Electronic Media, 2025)
Keywords: Citizenship; Engineering; Law; Political science; Public relations; Sociology; Work (physics); dept.aa

Considering the moment: Workforce development for the faculty–administrator transition - Milburn, Trudy; Winchatz, Michaela (Communication Education, 2026)
Keywords: Higher education; Job training; Transition (genetics); Transition countries; Workforce; Workforce development; dept.aa

Book Review: Culture 2.0: The Intersection of National and Organizational Culture and Unruly Speech: Displacement and the Politics of Transgression - Milburn, Trudy (Management Communication Quarterly, 2024)
Keywords: book review; dept.aa

Sword with a dual edge: Membership categorization and stereotyping in elite European club football commentary (chapter 12) - Hansen, Alan; Milburn, Trudy (Communicated Stereotypes at Work, 2024)
Communicated Stereotypes at Work highlights the pervasiveness and complexity of stereotypes in the workplace by analyzing the role they play in a variety of professional settings. Contributors exp...
Keywords: dept.aa

Communicating User Experience: Applying Local Strategies Research to Digital Media Design - Milburn, Trudy (2015)
Communicating User Experience illustrates how the use of Local Strategies Research (LSR) methodologies enables designers to understand the cultural implications for user actions and practices in a...
Keywords: dept.aa

Preface: Special Issue—College Experiences for Students with Autism Spectrum Disorder - Jackson, Scott L. J.; Hart, Logan; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
Keywords: dept.aa; dept.sed

Organizational communication scholars and U.S. higher education leadership: opportunities and challenges when scholars become administrators - Castor, Theresa; Milburn, Trudy; Eisenberg, Eric M.; Shockley-Zalabak, Pam (Management Communication Quarterly, 2025)
Universities and colleges are organizations that significantly impact students, their communities, and society. This forum explores how organizational communication scholars who are university leaders have applied their scholarly backgrounds to inform their roles. The forum participants engage in the work of being reflective practitioners to shed light on how organizational communication theory can help in negotiating the everyday lived experience of academic leadership. Three key issues are explored: (1) in what ways are organizational communication scholars uniquely positioned to assume a university leadership role? (2) how do communication concepts inform the communication practices of administrators? and (3) how do communication practices contribute to universities as multi-faceted institutions? The participants conclude by reflecting on current challenges in higher education and the potential of organizational communication scholars to play a vital role in navigating those challenges.
Keywords: dept.aa; peer-reviewed

Cultural discourse analysis: discourse hubs as heuristic devices - Carbaugh, D.; Milburn, T.; Scollo, M.; van Over, B. (The Routledge Handbook of Cultural Discourse Studies, 2024)
The purpose of this chapter is twofold; we first review our approach to cultural discourse analysis and then explicate the role of “discursive hubs” within it. The six discursive hubs we discuss are A Hub of Being: How is identity expressed? Acting: How do we express what we are doing? Relating: How do we express that we are related to each other? Feeling: How do we express what we feel? Dwelling: How do we express where we are (place) in our natural world (or material environment)? Timing: How do we express the understanding of process or sequencing over time? Our chapter brings to the fore several features of the general construct, discursive hub. Each feature of a hub adds an essential aspect to studies of cultural discourses. The set of features offers a systematic guideline for the design and execution of cultural discourse analytic studies into discursive hubs. Specifically, the set of features includes (a) The research question each hub raises; (b) the specific bits of discourse each concept of “discourse hub” makes relevant; (c) the socio-cultural functions of each hub within discourses or what that hub does within a discourse and (d) symbolic instantiations of that hub (in language, images, sounds and other signs) in actual cases of cultural discourse. Our discussion of the discourse hubs then turns to the heuristic role they play in the conduct of cultural discourse analyses. We emphasise that the hubs often work deeply together and thus their interrelationships breathe social life into cultural discourses. © 2024 selection and editorial matter, Shi-xu; individual chapters, the contributors.
Keywords: dept.aa

Engaging and transforming global communication through cultural discourse analysis: a tribute to Donal Carbaugh - Scollo, Michelle; Milburn, Tracy (2023)
The book is a handbook of cultural discourse analysis, a theory developed by Donal Carbaugh, and celebration of his work. The book features an explanation of the theory and sixteen chapters using ...
Keywords: dept.aa

The Borders in All of Us: New Approaches to Global Diasporic Societies - Little, William A.; Williams, Selase W.; Vásquez, Irene; Furusa, Munashe; Park, Jung-Sun (New World African Press, 2006)
Keywords: Emigration and immigration; History; dept.aa

Collected Articles of Selase W. Williams. - Williams, Selase W. (2005)
Keywords: African Americans; Languages; English language; United States; Creole dialects; Variation; dept.aa; faculty_collection

Leadership as Place - Beatty, Ellen; Page, Robert (Leadership in Place: How Academic Professionals Can Find Their Leadership Voice, 2007)
Keywords: Administration; Universities and colleges; Faculty; Educational leadership; United States; Universities and colleges; dept.aa; dept.mgt; faculty_collection

Brief Report: A Specialized Fitness Program for Individuals with Autism Spectrum Disorder Benefits Physical, Behavioral, and Emotional Outcomes - Jackson, S.L.J.; Abel, E.A.; Reimer, S.; McPartland, J.C. (Journal of Autism and Developmental Disorders, 2022)
Individuals with autism spectrum disorder (ASD) engage in less physical activity than typically-developing peers. This can result in serious negative consequences for individual well-being and may contribute to the physical, behavioral, and emotional challenges associated with ASD. This study explored the potential benefits of trainer-led, individualized, physical fitness sessions specialized for ASD. Eleven individuals (ages 7–24 years) with ASD were assessed at baseline and following 15 fitness sessions. Participants demonstrated improvements in core and lower-body strength and reductions in restricted and repetitive patterns of behavior, along with non-significant but marked reductions in issues with daytime sleepiness. Results suggest the merit of specialized fitness programs and emphasize the need for larger and more rigorous research studies on this topic. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
3 citations (Crossref) [2023-10-31]
Keywords: Autism spectrum disorder; Exercise; Fitness; Physical health; Restricted and repetitive behaviors; Sleep behaviors; dept.aa; dept.adm; peer-reviewed

Population study of laternula truncata (bivalvia: anomalodesmata: laternulidae) in the mangrove sand flat of kungkrabaen bay, thailand, with notes on laternula cf. corrugata - Prezant, R.; Sutcharit, C.; Chalermwat, K.; Duangdee, Teerapong (Proceedings of the International Marine Bivalve Workshop, Chanthaburi, Thailand, 2008)
Overall benthic macroinvertebrate biodiversity, along with laternulid density, was higher closer to mangroves but relative infaunal invertebrate dominance increased along a transect that transcended a hummock closer to the mangrove forest, across an open sand fl at, and terminated in another isolated humMock farther from the fringing forest. A population of the anomalodesmatan bivalve Laternula truncata (Lamarck, 1818) was examined in a mangrove sand fl at in Kungkrabaen Bay, Thailand, to determine population size, cohort distribution, and basic relationships with sediment and infaunal macroinvertebrate biodiversity. Relatively high densities of L. truncata were found in muddy sands, often deeply buried in or close to tangled rootlet mats of the mangrove trees Avicennia alba Blume, 1827, and A. marina (Forsskal) Vierhapper, 1907, along isolated mangrove hummocks. They were less common in open areas of the mangrove fl at. This population of L. truncata was relatively evenly distributed across size classes, minus the smallest sizes, suggesting continuous recruitment with a possible loss of recent recruits or recruitment. Overall benthic macroinvertebrate biodiversity, along with laternulid density, was higher closer to mangroves but relative infaunal invertebrate dominance increased along a transect that transcended a hummock closer to the mangrove forest, across an open sand fl at, and terminated in another isolated hummock farther from the fringing forest. A nearby population of L. cf. corrugata (Reeve, 1863) inhabited a distinctly different habitat. Laternula cf. corrugata was shallowly buried and dwelt in the mangrove forest proper among different species of mangroves and in sandier sediments. Behavioural observations of both laternulids indicated that both were capable of reburying, with smaller specimens more rapidly, albeit still slowly, succeeding in full re-entry into the sediment. Larger specimens of L. truncata were incapable of reburial. Morphological, ecological, and behavioural distinctions between L. truncata and L. cf. corrugata are considered in light of their habitat differences, confusion within laternulid systematics, and diffi culty in resolving the taxonomy of the latter species.
Keywords: dept.aa; ⛔ No DOI found

Effects of Upper-Limit Water Temperatures on the Dispersal of the Asian Clam Corbicula fluminea - Rosa, Inês Correia; Pereira, Joana Luísa; Costa, Raquel; Gonçalves, Fernando; Prezant, Robert (PLOS ONE, 2012)
Temperature is a determinant environmental variable in metabolic rates of organisms ultimately influencing important physiological and behavioural features. Stressful conditions such as increasing temperature, particularly within high ranges occurring in the summer, have been suggested to induce flotation behaviour in Corbicula fluminea which may be important in dispersal of this invasive species. However, there has been no experimental evidence supporting this hypothesis. It was already proven that C. fluminea drift is supported by a mucilaginous drogue line produced by mucocytes present in the ctenidia. Detailed microscopic examination of changes in these cells and quantification of clam flotation following one, two and three weeks of exposure to 22, 25 and 30°C was carried out so that the effects of increasing water temperatures in dispersal patterns could be discussed. Results show that changes in temperature triggered an acceleration of the mucocytes production and stimulated flotation behaviour, especially following one week of exposure. Dilution of these effects occurred following longer exposure periods. It is possible that these bivalves perceive changing temperature as a stress and respond accordingly in the short-term, and then acclimate to the new environmental conditions. The response patterns suggest that increasing water temperatures could stimulate C. fluminea population expansion.
23 citations (Crossref) [2023-10-31]
Keywords: Analysis of variance; Animal behavior; Behavior; Bivalves; Crystallization; Histology; Invasive species; Sediment; dept.aa; peer-reviewed

New England Town Meeting and the Cultivation of Deliberative Play - Townsend, Rebecca M.; Milburn, Trudy (American Behavioral Scientist, 2022)
Participants of New England town meeting must follow protocols to participate in this direct democratic process. Over the past 200 years, the protocols have been enacted and adapted by participants in small towns across the region. Within annual meetings, one can find small breaches that could be interpreted as playful acts. In this paper, we use the comic frame as a theoretical lens to interpret instances of such play within the rhetorical deliberation of one New England town meeting. We analyze two instances where speakers playfully use recognized parts of town meeting to achieve their rhetorical ends. We conclude with a discussion of the way play can help accomplish identification in public discourse.
1 citations (Crossref) [2023-10-31]
Keywords: dept.aa; peer-reviewed

Immigrant act - Crawford, I. (JAC: A Journal of Composition Theory, 2006)
Keywords: dept.aa; ⛔ No DOI found

The use of hi fidelity simulation to enhance nursing students' therapeutic communication skills - Sleeper, J.A.; Thompson, C. (International Journal of Nursing Education Scholarship, 2008)
Nursing students entering psychiatric settings for clinical practice need a solid foundation of therapeutic communication skills. This article presents an innovative strategy for nursing students to practice therapeutic communication skills with psychiatric patients by using hi fidelity simulation with Laerdal SimMan. Using the SimMan vocal function enabled nurse educators to develop communication algorithms that allowed students to interact with SimMan as they would with psychiatric patients. The SimMan algorithms can be designed to mimic many scenarios typically found in psychiatric settings. Nursing students can use this technology to take the therapeutic communication skills they have learned in the classroom and practice them in a safe laboratory environment before entering actual psychiatric settings. The ability of students to practice communication skills prior to entering psychiatric settings can promote effective therapeutic communication skills and decrease student anxiety. Copyright ©2008 The Berkeley Electronic Press. All rights reserved.
47 citations (Crossref) [2023-10-31]
Keywords: Communication; Psychiatric patients; SimMan; Teaching strategies; dept.aa

Growing routes: Rhetoric as the study and practice of movement - Crawford, I.W. (Rhetorica in Motion: Fem. Rhetorical Methods and Methodologies, 2010)
Journal Abbreviation: Rhetorica in Motion: Fem. Rhetorical Methods and Methodologies
Keywords: dept.aa

The emotional effects of literacy: Vietnamese women negotiating the shift to a market economy - Crawford, I.W. (Women and Lit.: Local and Glob. Inq. for a New Century, 2020)
Journal Abbreviation: Women and Lit.: Local and Glob. Inq. for a New Century
Keywords: dept.aa

Coded communities: organizing boundless diversity - Milburn, Trudy A. (Annals of the International Communication Association, 2021)
Communication researchers have used speech codes theory to interpret local conduct. This qualitative meta-analysis draws upon twenty years of peer-reviewed journal articles and books (2000–2019) that specifically use the concept of speech community within research about speech codes. Although speech community is incorporated into one of the six main tenets of speech codes theory, the concept has not been used consistently. After reviewing how speech codes theory researchers use the concept of speech community, I draw comparisons between those who describe mediated and intercultural practices to interrogate the a priori assertion of a speech community. I conclude by arguing that one must understand the particular social relations among speakers before asserting the existence of a speech community. © 2021 International Communication Association.
2 citations (Crossref) [2023-10-31]
Keywords: dept.aa; peer-reviewed; ⛔ No DOI found

Core dimensions of autism spectrum disorders - Volkmar, Fred R.; Jackson, Scott L.J. (New Oxford Textbook of Psychiatry, 2020)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder that manifests during the early developmental period of childhood. Behaviourally characterized by impairments in social interaction and communication, in combination with stereotyped and restricted patterns of behaviour and/or interest, it is currently believed that ASD occurs in approximately 1–2% of individuals. ASD is more prevalent among males than females (4–5:1), but the mechanisms resulting in this discrepancy are still unclear. This chapter will serve as an introduction to ASD, covering the topics of disorder history, prevalence rates, demographics, diagnostic criteria, differential diagnosis, and discussions on current and future diagnostic classification systems. The remaining chapters within Section 4 will then provide detailed discussions on more specific topics related to ASD, including current understandings of treatment planning, prevention and epidemiology, genetics, imaging, and disorder management.
tex.ids: volkmarCoreDimensionsAutism2020a
Keywords: dept.sed

Challenges of transitioning from a faculty to an administrative role: part 3, from solving problems to managing polarities. - Thompson, Cesarina M (Nurse Educator, 2011)
Many new nursing leaders assuming deanships, assistant, or interim deanships have limited education, experience, or background to prepare them for the job. To assist new deans and those aspiring to be deans, Jana L. Pressler, PhD, RN, and Carole A. Kenner, PhD, RNC-NIC, FAAN, the editors of this department, address common issues, challenges, and opportunities that face academic executive teams, such as negotiating an executive contract, obtaining faculty lines, building effective work teams, managing difficult employees, and creating nimble organizational structure to respond to changing consumer, healthcare delivery, and community needs. In this article, the editors asked guest author, Dr Cesarina Thompson, to discuss the transition process from faculty to administrative role.
3 citations (Crossref) [2023-10-31] Place: United States Thompson, Cesarina M. School of Health & Human Services, Southern Connecticut State University, New Haven, CT, USA.
Keywords: *Education; Nursing; *Efficiency; Organizational; *Faculty; Nursing; *Leadership; *Nurse Administrators; *Professional Role/px [Psychology]; Curriculum; Education; Nursing; Efficiency; Organizational; Faculty; Nursing; Humans; Leadership; Nurse Administrators; Professional Role; Time Factors; article; curriculum; dept.aa; human; leadership; nurse administrator; nursing education; organization and management; peer-reviewed; professional standard; psychological aspect; time

Challenges of transitioning from a faculty to an administrative role: part 2, moving from individual contributor to group leader. - Thompson, Cesarina M (Nurse Educator, 2011)
Many new nursing leaders assuming deanships, assistant, or interim deanships have limited education, experience, or background to prepare them for the job. To assist new deans and those aspiring to be deans, Jana L. Pressler, PhD, RN, and Carole A. Kenner, PhD, RNC-NIC, FAAN, the editors of this department, address common issues, challenges, and opportunities that face academic executive teams, such as negotiating an executive contract, obtaining faculty lines, building effective work teams, managing difficult employees, and creating nimble organizational structure to respond to changing consumer, healthcare delivery, and community needs. In this article, the editors asked guest author, Dr Cesarina Thompson, to discuss the transition process from faculty to administrative role.
1 citations (Crossref) [2023-10-31] Place: United States Thompson, Cesarina M. School of Health & Human Services, Southern Connecticut State University, New Haven, CT, USA.
Keywords: *Faculty; Nursing; *Group Processes; *Leadership; *Nurse Administrators; Education; Nursing; Faculty; Nursing; Group Processes; Humans; Leadership; Nurse Administrators; Schools; Nursing; Social Support; article; dept.aa; group process; human; leadership; nurse administrator; nursing education; peer-reviewed; social support

Transitioning from a faculty to an administrative role: part 1, moving from individual to collective accountability. - Thompson, Cesarina M (Nurse Educator, 2011)
Many new nursing leaders assuming deanships, assistant, or interim deanships have limited education, experience, or background to prepare them for the job. To assist new deans and those aspiring to be deans, Jana L. Pressler, PhD, RN, and Carole A. Kenner, PhD, RNC-NIC, FAAN, the editors of this department, address common issues, challenges, and opportunities that face academic executive teams, such as negotiating an executive contract, obtaining faculty lines, building effective work teams, managing difficult employees, and creating nimble organizational structure to respond to changing consumer, healthcare delivery, and community needs. In this article, the editors asked guest author, Dr Cesarina Thompson, to discuss the transition process from faculty to administrative role.
2 citations (Crossref) [2023-10-31] Place: United States Thompson, Cesarina M. School of Graduate Studies, Southern Connecticut State University, New Haven, USA.
Keywords: *Career Mobility; *Faculty; Nursing/og [Organization & Administration]; *Nurse Administrators/og [Organization & Administration]; *Professional Role; Career Mobility; Employee Performance Appraisal; Faculty; Nursing; Humans; Leadership; Nurse Administrators; Professional Role; United States; article; career mobility; dept.aa; human; leadership; nurse administrator; nursing education; organization and management; peer-reviewed; personnel management; professional standard

Handheld app offering visual support to students with autism spectrum disorders (ASDs) - Zamfir, Bogdan; Tedesco, Robert; Reichow, Brian (International Conference on Computers Helping People with Special Needs, 2012)
iPrompts® is a software application for handheld devices that provides visual support to individuals with Autism Spectrum Disorders (ASDs). Caregivers use the application to create and present visual schedules, visual countdown timers, and visual choices, to help individuals with ASDs stay organized, understand upcoming events, and identify preferences. The developer of the application, HandHold Adaptive, LLC, initially introduced iPrompts on the iPhone and iPod Touch in May of 2009. The research team from the Center of Excellence on Autism Spectrum Disorders at Southern Connecticut State University conducted a study of iPrompts in 2010, investigating its use by educators working with students with ASDs. Among other findings, educators indicated a desire to present visual supports on a larger, "tablet"-sized display screen, leading the developer to produce an iPad-specific product, iPrompts® XL. Described in this paper are the research effort of iPrompts and subsequent development effort of iPrompts XL. © 2012 Springer-Verlag.
7 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: ASD; Applications; Autism spectrum disorders; Diseases; Education; Hand held computers; Hand held device; Smartphones; app; application; autism spectrum disorder; dept.aa; handheld device; iPad; iPhone; iPrompts; smartphone; tablet

The potential of repetitive transcranial magnetic stimulation for autism spectrum disorder: A consensus statement - Cole, Eleanor J.; Enticott, Peter G.; Oberman, Lindsay M.; Gwynette, M. Frampton; Casanova, Manuel F.; Jackson, Scott L. J.; Jannati, Ali; McPartland, James C.; Naples, Adam J.; Puts, Nicolaas A. J.; Albein-Urios, Natalia; Barnett, Carol; et al. (Biological Psychiatry, 2019)
Autism spectrum disorder (ASD) affects approximately 1 in 59 children, but there are currently no biomedical treatments available that target the core symptoms (1). Preliminary evidence suggests that repetitive transcranial magnetic stimulation (rTMS) may have the potential to alleviate difficulties experienced by individuals with ASD (2). The evidence supporting the use of rTMS for ASD has led researchers in the field to form a consensus group that has met annually since 2014. Here we summarize discussions from the most recent meeting in May 2017, including recommendations for future research directions.
24 citations (Crossref) [2023-10-31]
Keywords: dept.aa; peer-reviewed

Mood Disorders in High-Functioning Autism: The Importance of Alexithymia and Emotional Regulation. - Morie, Kristen P; Jackson, Scott; Zhai, Zu Wei; Potenza, Marc N; Dritschel, Barbara (Journal of Autism and Developmental Disorders, 2019)
Individuals with autism spectrum disorder (ASD) often have co-morbid anxiety and depression. Alexithymia and emotion regulation difficulties are commonly seen in individuals with ASD and in mood disorders. We hypothesized that alexithymia and emotional regulation would mediate the relationship between autistic features and anxiety/depression symptom severity. We collected data about emotional regulation, alexithymia, autistic symptoms and depression/anxiety in a sample of 64 young adults with ASD. We constructed two serial multiple mediator models, using autistic features as the independent variable and anxiety/depression symptoms as outcome variables. The serial relationship between alexithymia and emotional regulation mediated associations between autistic features and depression and anxiety, separately. The findings suggest that targeting alexithymia may benefit therapies designed to alleviate mood disorders in ASD.
43 citations (Crossref) [2023-10-31] Place: United States Morie, Kristen P. Department of Psychiatry, Yale University School of Medicine, New Haven, CT, 06510, USA. kristen.morie@yale.edu. Morie, Kristen P. Child Study Center, Yale University School of Medicine, New Haven, CT, 06510, USA. kristen.morie@yale.edu. Jackson, Scott. Department of Psychiatry, Yale University School of Medicine, New Haven, CT, 06510, USA. Scott.Jackson@yale.edu. Jackson, Scott. Child Study Center, Yale University School of Medicine, New Haven, CT, 06510, USA. Scott.Jackson@yale.edu. Jackson, Scott. Office of Assessment and Analytics, Southern Connecticut State University, 501 Crescent Street, New Haven, CT, 06515, USA. Scott.Jackson@yale.edu. Zhai, Zu Wei. Department of Psychology, Middlebury College, Middlebury, VT, 05753, USA. Potenza, Marc N. Department of Psychiatry, Yale University School of Medicine, New Haven, CT, 06510, USA. Potenza, Marc N. Child Study Center, Yale University School of Medicine, New Haven, CT, 06510, USA. Potenza, Marc N. Department of Neuroscience, Yale University School of Medicine, New Haven, CT, 06510, USA. Potenza, Marc N. Connecticut Council on Problem Gambling, Wethersfield, CT, 06109, USA. Potenza, Marc N. Connecticut Mental Health Center, New Haven, CT, 06519, USA. Dritschel, Barbara. School of Psychology & Neuroscience, University of St Andrews, St. Andrews, Fife, KY16 9JP, UK.
Keywords: *Affective Symptoms/px [Psychology]; *Autism Spectrum Disorder/px [Psychology]; *Emotions; *Mood Disorders/px [Psychology]; ASD; Adolescent; Adult; Affective Symptoms; Affective Symptoms/ep [Epidemiology]; Aged; Alexithymia; Anxiety; Anxiety Disorders; Article; Asperger Syndrome; Asperger syndrome; Autism; Autism Spectrum Disorder; Comorbidity; Depression; Emotional regulation; Emotions; Female; Humans; Male; Middle Aged; Mood Disorders; Mood disorders; Self Report; Surveys and Questionnaires; Toronto Alexithymia scale; Young Adult; adolescent; adult; aged; alexithymia; anxiety; anxiety disorder; autism; comorbidity; controlled study; depression; dept.aa; dept.adm; emotion; emotional disorder; emotionality; female; human; major clinical study; male; mental health; middle aged; mood disorder; peer-reviewed; priority journal; psychology; questionnaire; self report; young adult

Microplastic abundances in a mussel bed and ingestion by the ribbed marsh mussel Geukensia demissa. - Khan, Matthew B; Prezant, Robert S (Marine Pollution Bulletin, 2018)
Human activities have generated large quantities of microplastics that can be consumed by filter-feeding organisms as potential food sources. As a result, organisms may experience marked reductions in growth and/or health. To date there has been no investigations connecting microplastics (MPs) with the critically important ribbed mussel Geukensia demissa. Here we examined MP abundances within a bed of G. demissa in New Jersey. Results indicate that MP densities ranged between 11,000-50,000pieces/m2. The abundance of larger MPs (5mm>=1mm) did not vary among sampling sites while the smaller MPs (<1mm) abundances did vary between sampling sites. These smaller MPs also accounted for 79% of MPs recovered from these sites. Based on the higher abundance of smaller MPs, we also investigated MP ingestion/rejection in a laboratory setting. These results confirmed that ribbed mussels can ingest MPs with negative consequences for the buoyancy of plastics rejected in feces and pseudofeces. Copyright © 2018 The Authors. Published by Elsevier Ltd.. All rights reserved.
39 citations (Crossref) [2023-10-31] Place: England Khan, Matthew B. Montclair State University, 1 Normal Avenue, Montclair, NJ 07043, USA; The Georgia Sea Turtle Center, Jekyll Island Authority, 214 Stable Road, Jekyll Island, GA 31527, USA. Electronic address: khanm11@montclair.edu. Prezant, Robert S. Department of Environment, Geography and Marine Sciences, Southern Connecticut State University, New Haven, CT 06515, USA. Electronic address: prezantr1@southernct.edu.
Keywords: *Bivalvia; *Plastics/an [Analysis]; *Waste Products/an [Analysis]; *Water Pollutants; Chemical/an [Analysis]; Animals; Article; Bivalvia; Contamination; Eating; Filter-feeding organisms; Geukensia demissa; Human activities; Humans; Ingestion; Ingestion (engines); Marine pollution; Microplastic; Microplastics; Molluscs; Mussel bed; New Jersey; Plastics; Sampling site; United States; Waste Products; Water Pollutants; Chemical; abundance; analysis; animal; animal experiment; animal tissue; bivalve; body fluids and secretions; controlled study; dept.aa; eating; feces; filter feeder; growth; human; human activities; ingestion; ingestion rate; marine pollution; marsh; microplastic; mussel; nonhuman; peer-reviewed; plastic; pseudofeces; sampling; unclassified drug; waste; water pollutant

Brief report: Self-reported academic, social, and mental health experiences of post-secondary students with autism spectrum disorder - Jackson, Scott L. J.; Hart, Logan; Brown, Jane Thierfeld; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
104 citations (Crossref) [2023-10-31]
Keywords: dept.aa; dept.sed

Visioning hope: embracing higher education's role with urban public charter schools - Bergeron, Bette S. (Urban Education, 2017)
The purpose of this study is to reflect on the evolution of a partnership between a university and urban charter high school serving a predominately African American population. Because of the author's embeddedness both as the researcher and participant member, this research assumes the paradigm of autoethnography. Reflections on key components of this evolution provide implications for teacher education, particularly in regard to a call for engagement between urban charter schools and educator preparation programs, and a challenge to higher education to analyze existing perceptions of public charter schools within a wider institutional mission to prepare educators for all children.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/030-392-571-564-728 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: African American students; charter school; dept.aa; high school; programs; teacher education; universities; urban education

Transition issues and challenges for youth with autism spectrum disorders - Volkmar, Fred R.; Jackson, Scott L. J.; Hart, Logan (Pediatric Annals, 2017)
49 citations (Crossref) [2023-10-31]
Keywords: dept.aa; dept.sed

Autism: Social communication disorder - Jackson, Scott Luther James (Encyclopedia of Autism Spectrum Disorders, 2017)
Keywords: dept.aa